Statistical Phylogenetic Tree Analysis Using Differences of Means - Arnaoudova, Elissaveta; Haws, David C.; Huggins, Peter; Jaromczyk, Jerzy; Moore, Niel; Schardl, Christopher; Yoshida, Ruriko (Frontiers in Neuroscience, 2010)
We propose a statistical method to test whether two phylogenetic trees with given alignments are significantly incongruent. Our method compares the two distributions of phylogenetic trees given by the input alignments, instead of comparing point estimations of trees. This statistical approach can be applied to gene tree analysis for example, detecting unusual events in genome evolution such as horizontal gene transfer and reshuffling. Our method uses difference of means to compare two distributions of trees, after mapping trees in a vector space. Bootstrapping alignment columns can then be applied to obtain p-values. To compute distances between means, we employ a "kernel method'' which speeds up distance calculations when trees are mapped in a high-dimensional feature space, e.g. splits or quartets feature space. In this pilot study, first we test our statistical method on data sets simulated under a coalescence model, to test whether two alignments are generated by congruent gene trees. We follow our simulation results with applications to various data sets of gophers and lice, grasses and their endophytes, and different fungal genes from the same genome. A companion toolkit, Phylotree, is provided to facilitate computational experiments.